2006
DOI: 10.1086/505201
|View full text |Cite
|
Sign up to set email alerts
|

Far-Ultraviolet Spectral Images of the Cygnus Loop

Abstract: We present far-ultraviolet (FUV) spectral images, measured at C IV λ1550, He II λ1640, Si IV+O IV] λ1400, and O III] λ1664, of the entire Cygnus Loop, observed with the Spectroscopy of Plasma Evolution from Astrophysical Radiation (SPEAR) instrument, also known as FIMS. The spatial distribution of FUV emission generally corresponds with a limb-brightened shell, and is similar to optical, radio and X-ray images. The features found in the present work include a "carrot", diffuse interior, and breakout features, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 36 publications
5
36
0
Order By: Relevance
“…Spectral resolution at the given line was employed as the width (FWHM) of the Gaussian function. The final image was constructed using the method of adaptive smoothing to increase the signal-to-noise ratio (S/N; Seon et al 2006). The Gaussian smoothing scale varied from 1.2Њ to 6Њ.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral resolution at the given line was employed as the width (FWHM) of the Gaussian function. The final image was constructed using the method of adaptive smoothing to increase the signal-to-noise ratio (S/N; Seon et al 2006). The Gaussian smoothing scale varied from 1.2Њ to 6Њ.…”
Section: Introductionmentioning
confidence: 99%
“…Adopting a distance of 900 pc to the target (Reich et al 1979), the line luminosities were calculated and listed along with the values of the Cygnus Loop ) and the Vela (Nishikida et al 2006) in Table 1. The X-ray luminosities (Shelton et al 2004;Seon et al 2006;Lu & Aschenbach 2000) are also shown for comparison. Line luminosities with <2σ significance are indicated by 1σ upper limits.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…c The value is from Shelton et al (2004) and the corresponding energy band is 0.11-2.04 keV. d The value is from Seon et al (2006) and the corresponding energy band is 0.1-4.0 keV. e The value is from Lu & Aschenbach (2000) and the corresponding energy band is 0.1-2.5 keV.…”
Section: Discussionmentioning
confidence: 99%
“…644 (Nishikida et al 2006) and the Cygnus Loop SNR (Seon et al 2006). Both Nishikida et al and Seon et al find that the spatial distribution of FUV emission cannot be simply predicted using visible Ha or X-ray emission maps.…”
Section: Supernova Remnants and Superbubblesmentioning
confidence: 99%